Odpowiedzi

  • Użytkownik Zadane
2010-01-03T15:49:49+01:00
3x-2y=5
y=2x-4

3x-2(2x-4)=5
2x-y=4

3x-4x+8=5
2x-y=4

-x=-3
2x-y=4

x=3
2*3-y=4

x=3
6-y=4

x=3
y=2
2010-01-03T15:52:56+01:00
3x-2y=5
2x-y=4

3x=5+2y |:3
2x-y=4

x=1⅔+⅔y
2(1⅔+⅔y)-y=4

x=1⅔+⅔y
3⅓+1⅓y-y=4

x=1⅔+⅔y
3⅓+⅓y=4

x=1⅔+⅔y
⅓y=⅔ |:⅓

x=1⅔+⅔y
y=2

x=1⅔+⅔*2
x=1⅔+1⅓
x=3
2010-01-03T16:30:50+01:00
3x -2y=5
2x-y=4


3x - 2y = 5
y = 2x - 4

3x - 2( 2x - 4 ) = 5
2x - y = 4

-x = - 3
2x - y = 4

x = 3
2 * 3 - y = 4

x = 3
6 - y = 4

x = 3
y = 2

Pozdrawiam :)